Menciptakan Memori Sejarah Secara Linier dengan Menggunakan Penerapan Arsitektur Historicism: Museum Daerah Bojonegoro - Birra Firmansyah; Suko Istijanto (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2023)
The museum is one of the places where these stories from the past are brought together in dioramas and their collections, so that these stories live on and can be interpreted in depth and detail by future generations. The museum itself is a place of discovery of relics of the past, where people can explore and travel through history, remembering the past in their hearts and minds. The Bojonegoro region has a history that is important enough to be remembered by the Bojonegoro people themselves. Therefor Bojonegoro needs the Museum to become a facility for protecting historical items to always remind the struggle of the Bojonegoro region itself and can become a means of recreation and edutourism for the Bojonegoro region.